The 2021 Mw 6.7 Khankh earthquake in the Khuvsgul rift, Mongolia - Battogtokh, Davaasambuu; Bayasgalan, Amgalan; Wang, Kang; Ganzorig, Davaasuren; Bayaraa, Jargalsaikhan (Mongolian Geoscientist, 2021)
A Mw 6.7 occurred at Lake Khuvsgul in northwestern Mongolia at 05:32:56 AM Ulaanbaatar time on the 12th of January 2021. The epicenter of the event was offshore south of the Doloon Uul peninsula around 30 km SSW of Khankh village. Shaking was felt within most of central and western Mongolia, including the capital city Ulaanbaatar 600 km from the epicenter. The earthquake appears to have ruptured the Khuvsgul fault along the western coast of Lake Khuvsgul. The earthquake is the largest in Mongolia since the Mw 6.3 Busiin Gol earthquake in 1991. Our research team from the Institute of Astronomy and Geophysics, Mongolian Academy of Sciences visited the epicenter area for 5 days soon after the earthquake and installed four broad-band seismic stations and searched the area for geological evidence of the earthquake. The location, azimuth, dip and depth of this earthquake defined by moment tensor solutions calculated by the international seismological centers and analysis of InSAR interferograms and field observations. The projected intersections of the east-dipping nodal planes with the surface for solutions of the international seismological centers and researchers correlate relatively well with the mapped strike and location of the old tectonic scarp of the Khuvsgul fault although we have not discovered any primary co-seismic surface rupture. The InSAR interferogram demonstrates the sharp discontinuity and fringes in the area between the Western Range and Doloon Uul peninsula which implies surface deformation. Aftershocks that have continued during the three months subsequent to the earthquake define overall strike of the mainshock rupture.